FID navigator‐based MR thermometry method to monitor small temperature changes in the brain of ventilated animals. (11th November 2014) - Boulant, Nicolas; Bottlaender, Michel; Uhrig, Lynn; Giacomini, Eric; Luong, Michel; Amadon, Alexis; Massire, Aurélien; Larrat, Benoît; Vignaud, Alexandre
<x xml:space="preserve">Abstract</x> An MR thermometry method is proposed for measuring in vivo small temperature changes engendered by external RF heat sources. The method relies on reproducible and stable respiration and therefore currently applies to ventilated animals whose breathing is carefully controlled. It first consists in characterizing the stability of the main magnetic field as well as the variations induced by breathing during a first monitoring stage. Second, RF heating is applied while the phase and thus temperature evolutions are continuously measured, the corrections due to breathing and field drift being made thanks to the data accumulated during the first period. The RF heat source is finally stopped and the temperature rise likewise is continuously monitored during a third and last stage to observe the animal cooling down and to validate the assumptions made for correcting for the main field variation and the physiological noise. Experiments were performed with a clinical 7 T scanner on an anesthetized baboon and with a dedicated RF heating setup. Analysis of the data reveals a precision around 0.1°C, which allows us to reliably measure sub‐degree temperature rises in the muscle and in the brain of the animal. Copyright © 2014 John Wiley & Sons, Ltd.